2013
DOI: 10.1186/1472-6882-13-149
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory activity of polysaccharides isolated from Clerodendrum splendens: Beneficial effects in experimental autoimmune encephalomyelitis

Abstract: BackgroundExtracts of leaves from Clerodendrum have been used for centuries to treat a variety of medicinal problems in tropical Africa. However, little is known about the high-molecular weight active components conferring therapeutic properties to these extracts.MethodsPolysaccharides from the leaves of Clerodendrum splendens were extracted and fractionated by ion exchange and size-exclusion chromatography. Molecular weight determination, sugar analysis, degree of methyl esterification, and other chemical cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 58 publications
0
27
0
Order By: Relevance
“…These results demonstrated that polysaccharide subfraction CSP-AU1, isolated from the Clerodendrum , was one of the most effective activators of cytokine production and activates monocyte/macrophages through the signalling cascades of TLR4, Akt2/3, GSK-3α/β, p38β, p38δ, p38γ, p70S6K1, RSK2, mTOR and AP-1/NK-κB. This data provides a real basis to demonstrate the benefi cial immune modulation activity of this plant (Kouakou et al 2013 (Kamel et al 2007 ). Formaldehyde is the main constituent of air pollution.…”
Section: Clerodendrum Splendens G Donmentioning
confidence: 75%
“…These results demonstrated that polysaccharide subfraction CSP-AU1, isolated from the Clerodendrum , was one of the most effective activators of cytokine production and activates monocyte/macrophages through the signalling cascades of TLR4, Akt2/3, GSK-3α/β, p38β, p38δ, p38γ, p70S6K1, RSK2, mTOR and AP-1/NK-κB. This data provides a real basis to demonstrate the benefi cial immune modulation activity of this plant (Kouakou et al 2013 (Kamel et al 2007 ). Formaldehyde is the main constituent of air pollution.…”
Section: Clerodendrum Splendens G Donmentioning
confidence: 75%
“…Monosaccharides such as alditol acetate derivatives were identified by gas chromatography (GC) using an Agilent 6850 gas chromatograph (USA) equipped with an HP‐5MS capillary column (30 m × 0.25 nm) with 5% phenylmethylsiloxane and a flame ionization detector. The analyses were carried out in the temperature range from 175 to 225°C at a rate of 3°C min – . Analysis of the monosaccharide composition of the polysaccharide fractions was performed by the alditol acetate method .…”
Section: Methodsmentioning
confidence: 99%
“…Natural products are one of the most popular sources of complementary and alternative medicines for preventing and treating inflammatory and immune disorders. It is known that polyionic polysaccharides, due to their ability to interact with the surface receptors of immune cells, can activate various pathways of immunological regulation in organisms …”
Section: Introuctionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, effects of polysaccharides might be mediated mainly through the toll-like receptors (TLR2 and TRL4), dectin-1 and scavenger receptors, as reported for other botanical polysaccharides (87). The high proportion of arabinose-rich polysaccharides and homogalacturonans and effects on phagocytosis by LPS-pretreated macrophages suggests interaction through TLR4 (88,89). Furthermore, the inhibition of zymosan phagocytosis in macrophages with no pretreatment suggest interaction mainly with dectin-1 and TLR2 (90).…”
Section: Effects Of Polysaccharides From Raw and Cooked Chayote Pulp mentioning
confidence: 94%